2018
DOI: 10.1002/ejp.1182
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of a naked plasmid (pUDK‐HGF) encoding human hepatocyte growth factor attenuates skin/muscle incision and retraction‐induced chronic post‐surgical pain in rats

Abstract: The CPSP occurs following various surgical procedures and remains a major clinical problem due to the lack of study on the mechanisms of CPSP. Our findings provide the first evidence that pUDK-HGF attenuates SMIR-induced pain behaviuors through peripheral or central mechanisms. The peripheral analgesic effect of pUDK-HGF is associated with promoting tissue repair and inhibiting inflammatory response; furthermore, pUDK-HGF inhibits activation of spinal glial cells and overexpression of inflammatory mediators in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Our preclinical study indicated that angiogenesis is the mechanism underlying the analgesic action of pUDK-HGF, whereby the establishment of collateral circulation occurs [13,14]. Our recent work indicated that intramuscular injections of pUDK-HGF promote blood ow and proliferation of satellite cells, and inhibit in ammatory cell recruitment, collagen accumulation, and the expression of pronociceptive factors in a rat skin/muscle incision and retraction model [18,19] . Intrathecal injection of pUDK-HGF inhibited spinal glial cell activation and reduced the cytotoxicity associated with expression of interleukin (IL)-1β, IL-6, tumor necrosis factor α and inducible NO synthase, as well as decreasing nitric oxide production from activated glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our preclinical study indicated that angiogenesis is the mechanism underlying the analgesic action of pUDK-HGF, whereby the establishment of collateral circulation occurs [13,14]. Our recent work indicated that intramuscular injections of pUDK-HGF promote blood ow and proliferation of satellite cells, and inhibit in ammatory cell recruitment, collagen accumulation, and the expression of pronociceptive factors in a rat skin/muscle incision and retraction model [18,19] . Intrathecal injection of pUDK-HGF inhibited spinal glial cell activation and reduced the cytotoxicity associated with expression of interleukin (IL)-1β, IL-6, tumor necrosis factor α and inducible NO synthase, as well as decreasing nitric oxide production from activated glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that fibroblast growth factor (38,39) and hepatocyte growth factor (40,41) can reduce pain by inhibiting the activation of astrocytes in the spinal cord; and PRP contains various growth factors, including fibroblast growth factor and hepatocyte growth factor (42), so a longterm higher concentration of PRP acts on cells or may make such inhibitory effects more obvious Traditional studies have suggested that peripheral and central sensitization causes chronic pain due to changes in neuronal plasticity. However, recent studies have found that glial cells, especially astrocytes, play an essential role in maintaining chronic pain (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…A rat model of SMIR developed by Flatters [10] was usually used for investigating the underlying mechanism of postsurgical pain [1113]. Our study expanded this model from rat to mouse.…”
Section: Discussionmentioning
confidence: 99%
“…All of these procedures involve essential and prolonged tissue retraction, which could account for the persistent nature and high incidence of postsurgical pain. A new model of persistent postsurgical pain evoked by skin/muscle incision and retraction (SMIR) in rats invented by Flatters [10] was used widely for investigating the underlying mechanism of CPSP [1113]. Therefore, developing a new SMIR model in mice is necessary for further investigation with transgenic mice and so on.…”
Section: Introductionmentioning
confidence: 99%